Response of existing rubber bearing and designed base isolator for malaysian highway bridges - Ramli, Mohd. Zamri (2006)

(untitled)
In structural earthquake engineering, natural rubber and steel are used as base isolators for energy dissipation systems to reduce earthquake effect on structures. With laminated natural rubber and steel, the bearing can provide high vertical stiffness and flexibility in horizontal direction to ensure the mounts can support the loading from the structure and prevent excessive sideways from any horizontal loading especially when earthquake occur. This research performs the study of performance of Public Works Department (PWD) standard bridges under low intensity earthquake effect. The finite element modelling technique was used in this study to learn the behaviour of rubber bearing with various dimensions and directions of loading (vertical and horizontal). Performances of the rubber bearing were examined based on their stiffness factors. Seismic isolator is designed and it is found that the usage of designed seismic isolator increases the overall performance of the PWD Bridge. In general, this research indicates that the seismic risks should be considered in design the bridge for Malaysian.